The experience of grandparents of children hospitalized in Pediatric Intensive Care Unit - Moraes, Erika Sana; Mendes-Castillo, Ana Marcia Chiaradia (Revista da Escola de Enfermagem da USP, 2019)
Objective: To understand the experience of grandparents of children hospitalized in pediatric intensive care units. Method: This was a qualitative study based on the symbolic interactionism theoretical framework and the grounded theory as methodological framework carried out with grandparents of children hospitalized in the pediatric intensive care unit of a teaching hospital in a city in the state of São Paulo. Data were collected by means of participatory observation and semi-structured interviews, and analyzed following the open and axial codification stages of grounded theory. Results: Nine grandparents were interviewed. Two phenomena were identified: “finding themselves inside a storm” and “fighting to be the anchor of the family”, which explain the suffering experienced and support role developed by grandparents during the hospitalization period. Conclusion: Grandparents develop an important family support role during the crisis. Therefore, family care strategies must be developed to include this generation of the family, who are increasingly present and participatory in several healthcare settings.